2020
DOI: 10.1371/journal.pone.0238203
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C prevalence in Denmark in 2016—An updated estimate using multiple national registers

Abstract: Background Chronic hepatitis C (CHC) can be eliminated as a public health threat by meeting the WHO targets: 90% of patients diagnosed and 80% treated by 2030. To achieve and monitor progress towards elimination, an updated estimate of the size of the CHC population is needed, but Denmark has no complete national CHC register. By combining existing registers in 2007, we estimated the population living with CHC to be 16,888 (0.38% of the adult population). Aim To estimate the population living with diagnosed an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 26 publications
1
34
0
1
Order By: Relevance
“… 16 In 2015, the estimated prevalence of people with HCV and active infection (ie, viraemic) was 0.3% 17 and at the end of 2016 the population living with diagnosed chronic HCV was 7581 people, of which the estimated undiagnosed fraction was 24% and so the total diagnosed and undiagnosed number was estimated to be 9975, corresponding to 0.21% of the adult population. 18 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 16 In 2015, the estimated prevalence of people with HCV and active infection (ie, viraemic) was 0.3% 17 and at the end of 2016 the population living with diagnosed chronic HCV was 7581 people, of which the estimated undiagnosed fraction was 24% and so the total diagnosed and undiagnosed number was estimated to be 9975, corresponding to 0.21% of the adult population. 18 …”
Section: Introductionmentioning
confidence: 99%
“…16 In 2015, the estimated prevalence of people with HCV and active infection (ie, viraemic) was 0.3% 17 and at the end of 2016 the population living with diagnosed chronic HCV was 7581 people, of which the estimated undiagnosed fraction was 24% and so the total diagnosed and undiagnosed number was estimated to be 9975, corresponding to 0.21% of the adult population. 18 In the city of Copenhagen, drug treatment centres have been obliged to offer HCV testing for all PWID, following the adoption of the 2007 Danish action plan for HCV in PWID. 19 However, testing uptake has been suboptimal, and it has only recently been encouraged through the Shared Addiction Care Collaboration.…”
mentioning
confidence: 99%
“…In addition, diagnostic coverage and linkage of susceptible populations to treatment and care have been known to be low globally [ 8 ]; indeed, research reported in this collection suggests that these shortcomings still exist. For example, Nielsen and colleagues report that over 50% of HCV positive patients in Denmark had yet to attend specialist care, especially in regions with a likely higher rate of intravenous drug use [ 9 ]. In Australia, Hanson and colleagues report that both HBV-related and other liver-related deaths were more common in indigenous Australians when compared to the non-indigenous population [ 10 ], suggesting that hurdles still exist in providing quality healthcare to indigenous populations living with HBV in remote areas.…”
Section: Research Highlightsmentioning
confidence: 99%
“…If none of the three survey approaches are possible there are several alternative methods to consider, although these methods may be more subject to potential bias. These include testing residual sera from laboratory samples (16,17), samples from proxy populations of the general population such as pregnant women (18) or first-time blood donors (6) or general practitioner or health insurance registries as well as linking information from multiple national registries and applying various modeling techniques (19,20). These and more FIGURE 2 | Decision algorithm to select the most suitable survey approach when planning a prevalence survey for hepatitis C in the general population (15).…”
Section: Selecting a Survey Approachmentioning
confidence: 99%
“…More data and additional methodological approaches are needed in order to generate a national prevalence estimate. Some countries have combined data from multiple registers and applied various modeling techniques to generate national HCV prevalence estimates (20,31). Others have applied the workbook method (32) or the Bayesian multi-parameter evidence synthesis (MPES) (33).…”
Section: Moving From Hcv Prevalence Estimate In General Population To National Prevalence Estimatementioning
confidence: 99%